Preferences, Needs, and Demand Analysis of Health Facilities Development - Gusniawan, Rino Indira; Kumalasari, Berti; Azizah, Yasmin (Journal of Consumer Sciences, 2023)
Health is one aspect that determines human living standards. Health is needed to support all life activities, and health facilities are required to provide a healthy community. This study aimed to identify and analyze the relationship between preferences, needs, and demands for developing health facilities in Bogor City. Data were collected in May 2023. A total of 201 research respondents participated in the study. The relationship test showed that the mother's occupation and preference had a significant positive relationship with the level of interest, and the mother's employment and level of interest had a significant positive relationship with the level of need. Monthly family expenditure had a significant negative association with the level of need, mother’s age had a significant negative relationship with the demand for the construction of health facilities, and family size and grade of importance had a significant positive relationship with the demand for health facility development.